Dividing the pie: A quantitative review on plant density responses. (29th December 2020) - Postma, Johannes A.; Hecht, Vera L.; Hikosaka, Kouki; Nord, Eric A.; Pons, Thijs L.; Poorter, Hendrik
Abstract: Plant population density is an important variable in agronomy and forestry and offers an experimental way to better understand plant–plant competition. We made a meta‐analysis of responses of even‐aged mono‐specific stands to population density by quantifying for 3 stand and 33 individual plant variables in 334 experiments how much both plant biomass and phenotypic traits change with a doubling in density. Increasing density increases standing crop per area, but decreases the mean size of its individuals, mostly through reduced tillering and branching. Among the phenotypic traits, stem diameter is negatively affected, but plant height remains remarkably similar, partly due to an increased stem length‐to‐mass ratio and partly by increased allocation to stems. The reduction in biomass is caused by a lower photosynthetic rate, mainly due to shading of part of the foliage. Total seed mass per plant is also strongly reduced, marginally by lower mass per seed, but mainly because of lower seed numbers. Plants generally have fewer shoot‐born roots, but their overall rooting depth seems hardly affected. The phenotypic plasticity responses to high densities correlate strongly with those to low light, and less with those to low nutrients, suggesting that at high density, shading affects plants more than nutrient depletion. Abstract : We present a meta‐analysis of the response of 36 stand and plant traits to increasing plant density in mono‐specific stands. High‐density plants have a phenotype similar to that of low‐light plants.